Bohai Sea Environmental Management Project. (Bohai Sea Environmental Management Project of the People?s Republic of China and GEF/UNDP/IMO Regional Programme on Building Partnerships in Environmental Management for the Seas of East Asia (PEMSEA), 2005)
PEMSEA Technical Report no. 12